Mutational Analysis of VIM-2 Reveals an Essential Determinant for Metallo-β-Lactamase Stability and Folding - Borgianni, Luisa (American Society for Microbiology (ASM), 2010)
Metallo-β-lactamase (MBL)-producing bacteria are emerging worldwide and represent a formidable threat to the efficacy of relevant β-lactams, including carbapenems, expanded-spectrum cephalosporins, and β-lactamase inactivator/β-lactam combinations. VIM-2 is currently the most widespread MBL and represents a primary target for MBL inhibitor research, the clinical need for which is expected to further increase in the future. Using a saturation mutagenesis approach, we probed the importance of four residues (Phe-61, Ala-64, Tyr-67, and Trp-87) located close to the VIM-2 active site and putatively relevant to the enzyme activity based on structural knowledge of the enzyme and on structure-activity relationships of the subclass B1 MBLs. The ampicillin MIC values shown by the various mutants were affected very differently depending on the randomized amino acid position. Position 64 appeared to be rather tolerant to substitution, and kinetic studies showed that the A64W mutation did not significantly affect substrate hydrolysis or binding, representing an important difference from IMP-type enzymes. Phe-61 and Tyr-67 could be replaced with several amino acids without the ampicillin MIC being significantly affected, but in contrast, Trp-87 was found to be critical for ampicillin resistance. Further kinetic and biochemical analyses of W87A and W87F variants showed that this residue is apparently important for the structure and proper folding of the enzyme but, surprisingly, not for its catalytic activity. These data support the critical role of residue 87 in the stability and folding of VIM-2 and might have strong implications for MBL inhibitor design, as this residue would represent an ideal target for interaction with small molecules.